Experimental Approach of Various Controller Tuning Methods for Integrating Processes With Dead Time (Journal of Informatics and Mathematical Sciences, 2019)
PID control is widely used in industrial control systems in order to adjust the controller gains according to change in plants. In this proposed work, controller tuning is performed automatically based on various tuning formula. The responses of various tuning methods for integrating process are analyzed for process with dead time.
Keywords: Tuning; PID Control; Dead time; Controller; Inergrating process